Implementasi Peraturan Walikota Pekanbaru Nomor 32 Tahun 2013 Tentang Pencegahan dan Penanggulangan HIV dan AIDS di Kota Pekanbaru - Putri, Radilla Armanda; Hadi, Ahmad (Innovative: Journal Of Social Science Research, 2025)
The city of Pekanbaru ranks first in terms of HIV/AIDS cases in Riau Province. The purpose of this study is to analyze the implementation of Pekanbaru Mayor Regulation Number 32 of 2013 on HIV and AIDS prevention and control efforts in the city of Pekanbaru, with a focus on prevention efforts coordinated by the Pekanbaru City KPA. This study uses a qualitative descriptive method with a case study approach. The theoretical concept used is the Edward III policy implementation model as quoted by Winarno (2014) which includes indicators of communication, resources, disposition, and bureaucratic structure. Data collection techniques include observation, interviews, and documentation conducted with key informants. The results of the study indicate that the implementation of prevention efforts coordinated by the Pekanbaru City KPA has been carried out through coordination between units in formulating HIV/AIDS prevention strategies, socialization, education, and promotion of behavioral change through online media, mass media, and social media. However, there are still several obstacles such as the absence of a strategic plan, lack of face-to-face socialization with the community, and the persistence of stigma and social discrimination against PLWHA. Therefore, there is a need to strengthen coordination among stakeholders and conduct evaluation and monitoring of program implementation to ensure that HIV/AIDS prevention policies in Pekanbaru City are implemented more effectively.